Agricultural youth injuries: An updated review of cases from U.S. news media reports, 2016-2021 - Bryan P. Weichelt; Serap Gorucu; Rick R. Burke; Marsha A. Salzwedel; Dennis J. Murphy; Barbara C. Lee (Frontiers Media S.A., 2022)
IntroductionFatal and non-fatal youth (ages 0-17) injuries in U.S. agriculture continue to be a significant public health concern. Despite sustained work and attention from federally supported research programming, we continue to observe an unacceptably high number of life-altering and life-ending traumatic injuries to youth in agricultural environments. Likewise, there is still a gap in stringent systematic agricultural injury and/or illness surveillance at the federal level. This paper will provide an updated review of child agricultural injuries from U.S. news media reports, expanding upon this author team's initial 2018 report.MethodsData collection from 2016 to 2021 occurred as part of the AgInjuryNews initiative, and data were coded according to the Farm and Agricultural Injury Classification (FAIC) system and the Occupational Injury and Illness Classification System (OIICS). The AgInjuryNews system primarily contains news media reports. Categorical variables were analyzed and compared using a chi-square test. In addition, the Jonckheere-Terpstra test for trend was used to test the yearly change in the number of youth injuries.ResultsWe observed a general decrease in agricultural injuries compared to the original 2015-2017 dataset. Younger children (<5 years-old) and males were more often injured and more fatally injured than older children and females, respectively. Males and older victims were more likely to suffer an occupational-related injury compared to females and younger victims, respectively. Vehicles remained a major source of injuries, with tractors comprising 28%, and ATVs/UTVs comprising 26% of all injuries. Roadway incidents involving tractors and UTVs were less often fatal compared to non-roadway incidents, while ATVs were more fatal on roadways.DiscussionThis updated review shows childhood agricultural injuries and fatalities continue to be a major public health concern within the US. It is unclear if the trend downward in injuries is due to reporting, data capture methods, or a true decrease in injuries. These data continue to be of interest to stakeholders in academia, public health, government, and private industry-user groups who regularly and consistently seek this type of information, often from multiple data sources, including as registered users on AgInjuryNews.org. These data identify emerging issues within the industry and further inform national and international planning committees' work.